paper Effective Detection of Amblyopia Risk Factor Using Smart Phone Eye Testing Application: -- (International Journal of Engineering and Computer Science, 2023)
Amblyopia also called as lazy eye. In this disease there is week communication between human eyes with human brain. Due to this reason one of the eye is not working properly compare to other eye. Amblyopia starts in early childhood, and most of the children are loss his vision. In the world 3 to 4 child’s are affected of amblyopia risk factors out of 100 children. If we give the early treatment on affected eye may be prevents long-term vision problems. This problem is focus in mind and author is doing study to accurately identify children at risk for amblyopia by using existing application from smartphone platforms. This study is not replace the advice of doctors on any condition.Keywords: Amblyopia Risk Factor, Visual Acuity Test,